Research progress of Traditional Chinese and Zhuang medicine in the treatment of postoperative pain after anterior cruciate ligament reconstruction (中医壮医治疗前交叉韧带重建术后疼痛的研究进展) - WEI Jiajia (韦佳佳); LIU Shuang (刘霜); MO Lilu (莫理璐); HUANG Biqiu (黄碧秋) (中西医结合护理, 2023)
Anterior cruciate ligament (ACL) reconstruction remains the gold standard for ACL. However, it may seriously impair the postoperative recovery. This paper summarized the integrated Traditional Chinese and western medicine and Zhuang medicine ironing therapy in the treatment of postoperative pain after anterior cruciate ligament reconstruction, and provided reference for further exploration of new technologies for clinical postoperative pain management. (前交叉韧带重建手术(ACL-R)是前交叉韧带损伤(ACL)临床治疗的金标准。ACL-R术后疼痛严重影响患者康复。本研究就ACL-R术后疼痛中西医干预方法以及壮医药熨疗法进行综述, 旨在为临床术后镇痛方案提供更多参考。)